Contribution of arm explosive power hand reaction speed to badminton smash ability - Irsan Kahar; Rachmat Hidayat; Ahmad Ahmad (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
This research aims to discover these problems, (1) Is there a contribution of arm power explosive to the smash ability of UM Palopo badminton athletes (UKM)? (2) Is there any contribution of hand reaction speed to the smash-hitting ability strength of UM Palopo badminton athletes (UKM)? (3) Is there any contribution of arm explosive power to hand reaction speed to the smash ability of UM Palopo badminton athletes (UKM)? Two independent variables and one dependent variable form this research. It is a descriptive research Sample and the population is athletes from UKM Badminton UM Palopo, by random sampling, 40 people were obtained. The data analysis technique used is Regression-Test (R). (1) Arm explosive power makes a sizable contribution to the smash-hitting ability of badminton Where the obtained value = 0.512 (p < 0.05), with a contribution or contribution of 57. 80% (2). There is a significant contribution of hand reaction speed to the ability to smash in badminton. The value = -0.4 61 (p < 0.05), with a contribution or contribution of 54.20 % (3). There is a significant contribution of explosive power, and arm reaction speed, to the smash ability of badminton. Where the value of Ro = 0.854 (P < 0.05), with a contribution or contribution of 72.90%.